HIV/Aids na velhice : a fala dos idosos soropositivos na cidade do Recife - Costa, Juliana Monteiro (2013)
Although aging is a biological reality, the meanings attributed to it are social and historical constructions. The increase in cases of HIV/Aids among people over sixty years has been reported by researchers because the data show an increase in cases proportion of HIV/Aids among older adults compared with other age groups. Among the reason for this increase is the misinformation of this public regarding the self-care, greater avaliability of drugs for erectile dysfunction, low use of condoms in this generation and delayed diagnosis. The objective of this study was to understand the meaning and implications of the biopsychosocial experience of living with HIV/Aids for the elderly in the city of Recife. Participated in nine elders (four females and five males), an age comprised between 60 and 76 years, living in Recife who were in treatment and/or monitoring the SAE (Service Specializing in Assisting HIV/Aids) of Polyclinic Lessa de Andrade. The survey was conducted in a semi-directed, organized from a script previously drafted, which were recorded and transcribed. The most significant results showed: the impact of the diagnosis of HIV/Aids accompanied by feelings of anger, guilt, embarrassment, fear, prejudice and abandonment by family, friends and neighbors that are part of everyday life of the elderly; an ontological dimension of sexuality, breaking the stereotype of old age marked by assexuality, gathering and passivity, the constructions of gender and social representation of Aids associated as the disease of the older as determining factors for the perceived invulnerability to HIV/Aids among people in this age group; spirituality as support, something that came to appease the pain and suffering in the face of positive sorology for HIV; compromised physical health of the elderly due to the gradual and progressive destruction of the body's defense cells associated with old age; lack of preparation on the part of the healthcare team to deal with HIV / AIDS in this age group, resulting in late diagnosis. This work had therefore the aim of contributing to illiminate the field knowledge and practices whose horizon of ethical concerns and policies to reduce vulnerability of the elderly to HIV/Aids.